Persepsi Pengguna Sebagai Dasar Pengembangan Model Usability Aplikasi Mobile Commerce - Hutahaean, Hotma Antoni; silalahi, Agustinus; Prabu Hidayat, Trifenaus; Sukwadi, Ronald; Kartawidjaja, Maria Angela (Metris: Jurnal Sains dan Teknologi, 2024)
The intense competition between developers, resulting in efforts to determine users' needs, is increasingly important. Usability An application can affect the continuity of application use. In this study, the user's loyalty is also used to analyze usability. This study examines user perceptions about user interaction characteristics when interacting with the mobile commerce application and considers users' loyalty. This research is essential to find out the needs of users of a mobile commerce application, which can be input to the developer in the design stage. This study uses 149 respondents' online shopping transactions in Jabadetabek and outside Jabodetabek, Indonesia. Data were analyzed using the Structural Equation Modeling (SEM) model. The results showed that users' perception of effectiveness, satisfaction, and learning influenced usability. This model can explain 42.6% of the user's usability variation when using it. This model can explain the usability of the Mobile Commerce application quite well. As a practical implication, this study shows the factors that support the characteristics of user interaction and application systems at the stage of defining the requirements for developing mobile commerce applications.